Anticipating Balance of Payments Crises--The Role of Early Warning Systems - Pattillo, Catherine; Berg, Andrew; Borensztein, Eduardo..; Milesi-Ferretti, Gian. (Washington, D.C. : International Monetary Fund, 2000)
Recent years have witnessed an increase in the frequency of currency and balance of payments crises in developing countries. More important, the crises have become more virulent, have caused widespread disruption to other developing countries, and have even had repercussions on advanced economies. To predict crises, their causes must be clearly understood. Two competing strands of theories are reviewed in this paper. The first focuses on the consequences of such policies as excessive credit growth in provoking depletion of foreign exchange reserves and making a devaluation enevitable. The second emphasizes the trade-offs between internal and external balance that the policymaker faces in defending a peg.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Capital and Ownership Structure; Financial Risk and Risk Management; Financing Policy; Goodwill; Value of Firms